Analisis pengaruh pengungkapan sustainability report, kinerja keuangan, dan kinerja lingkungan terhadap nilai perusahaan - Aristha Purwanthari Sawitri; Nurcholis Setiawan (STIE Perbanas Surabaya, 2017)
The goal of peneliitian is to look at the effect of disclosure of the sustainability report, the financial performance and environmental performance of companies. The sample of this research is a company entered in the index 30 in 2012 until the year 2016 and sampling method using a purposive sampling. The results of this study found that the sustainability report has no effect against the value of the company, the same result in-show by a variable performance environment where environmental performance does not affect the value of the as for the company's financial performance variables have significant influence towards the value of the company.